Food Processing Sector in India and Its Role in Livelihood Generation - Bora , Mayuri; Baruah , Anubhuti (Current Perspectives in Agriculture and Food Science Vol. 6, 2023)
The book chapter intends to present the current scenario of food processing sector in India with special focus on Assam which is a North Eastern state of the country. Food processing sector though considered as potential growth engine of the nation because of several factors, yet it has not contributed significantly owing to some bottlenecks. The chapter also highlights the present scenario of food processing in India, Government initiative for growth of the sector with various objectives targeting different segments. The SWOT analysis of the food processing sector in India presented in the chapter throws light on different perspective including the responsibility of concerned agencies as well as the food processors for growth of the sector. Role of the regulatory body for food safety and quality control in the food processing units also finds place in the chapter.